2012
DOI: 10.1097/olq.0b013e318249d90f
|View full text |Cite
|
Sign up to set email alerts
|

Results of a 25-Year Longitudinal Analysis of the Serologic Incidence of Syphilis in a Cohort of HIV-Infected Patients With Unrestricted Access to Care

Abstract: Background The well described biological and epidemiologic associations of syphilis and HIV are particularly relevant to the military, as service members are young and at risk for sexually transmitted infections. We therefore used the results of serial serologic testing to determine the prevalence, incidence, and risk factors for incident syphilis in a cohort of HIV-infected Department of Defense beneficiaries. Methods Participants with a positive non-treponemal test at HIV diagnosis that was confirmed on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
18
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
6
18
2
3
Order By: Relevance
“…Our overall findings are consistent with reported occurrences of other STIs among HIV-positive persons in the NHS cohort, such as syphilis,28 and are consistent with STI rates in the US military 29. A recent study of the general US military population found a similar rate of CT at 11.4 per 1000 PY and a lower rate of GC at 1.98 per 1000 PY 2–10.…”
Section: Discussionsupporting
confidence: 90%
“…Our overall findings are consistent with reported occurrences of other STIs among HIV-positive persons in the NHS cohort, such as syphilis,28 and are consistent with STI rates in the US military 29. A recent study of the general US military population found a similar rate of CT at 11.4 per 1000 PY and a lower rate of GC at 1.98 per 1000 PY 2–10.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, enrolled subjects may visit other clinics for STD treatments, lowering the estimated STD incidence. Nevertheless, the STD rate reported here is similar to that reported in previous studies, 12,14,15,21,24,25,42,43 and represents the current scenario in Taiwan.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, several reports of increasingly risky sexual behaviors in the HIV-positive population in the post-HAART era have been published. [9][10][11][12][13][14][15] Therefore, the use of HAART for HIV prevention is facing significant challenges.…”
mentioning
confidence: 99%
“…10-12 A long-term study conducted among US military personnel found that 5.8% of 4239 newly diagnosed HIV infections also had serological evidence of syphilis infections. 13 Increased prevalence of syphilis-HIV coinfections in young MSM was also reported in other regions of the world. [14][15][16][17] Whilst HIV is known to affect the course of syphilis, early syphilis also affects markers of HIV infection.…”
Section: Discussionmentioning
confidence: 83%